2013
DOI: 10.1044/1058-0360(2013/12-0076)
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Discourse Deficits Following Penetrating Head Injury: A Preliminary Model

Abstract: In spite of differing mechanisms of injury, the PHI group's discourse performance was consistent with what has been reported for individuals with CHI. The model tested represents a preliminary step toward understanding discourse production following traumatic brain injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 41 publications
5
58
0
2
Order By: Relevance
“…This finding is partially consistent with the literature. It is coherent with some findings [10,12,14,38] but not with others [13,17]. For example, Marini et al [13] considered different aspects of productivity (words, speech rate, and mean length of utterance), showing that a group of non-aphasic participants with severe TBI produced narratives with a normal number of words and an adequate mean length of utterance but suggesting that these individuals might experience problems with the speech rate.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This finding is partially consistent with the literature. It is coherent with some findings [10,12,14,38] but not with others [13,17]. For example, Marini et al [13] considered different aspects of productivity (words, speech rate, and mean length of utterance), showing that a group of non-aphasic participants with severe TBI produced narratives with a normal number of words and an adequate mean length of utterance but suggesting that these individuals might experience problems with the speech rate.…”
Section: Discussionsupporting
confidence: 79%
“…It is then likely that what they had heard provided them with significant cues for producing more complex utterances [42]. In some other studies, the sentence complexity-related discourse of individuals with brain injury did not differ from that of a group of healthy controls [10,18,43]. The disparity in syntactic performance between studies might be due to differences between the type of scaling complexity or task differences [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies evaluating other high-level cognitivecommunicative functions in the TBI population, such as listening comprehension and discourse production, provide further empirical support for predicting breakdowns at different levels of reading comprehension (e.g., Chapman et al, 1992;Coelho, 2002;Coelho et al, 2013;Moran & Gillon, 2005;Moran, Kirk, & Powell, 2012;Tompkins, Bloise, Timko, & Baumgaertner, 1994). Ferstl, Walther, Guthke, and Von Cramon (2005) compared the narrative listening comprehension abilities of four groups: adults with left-hemispheric brain damage (n = 18), adults with right-hemispheric brain damage (n = 12), adults with traumatic brain damage (n = 34), and uninjured controls (n = 49).…”
Section: Interactive Activation (Ia) Model Of Reading Comprehensionmentioning
confidence: 99%
“…Cognitive processes and domains, such as working memory (WM), declarative memory, executive functions (EF), and general intelligence have been shown to correlate with or predict narrative ability at multiple levels of analysis (e.g., Cannizzaro & Coelho, 2012;Chapman et al, 2006;Coelho et al, 2013;Kurczek & Duff, 2011;Wright, Capilouto, Srinivasan, & Fergadiotis, 2011). Studies of narrative discourse ability in healthy aging populations have found that performance on global (i.e., macro-level) measures is correlated with age and performance on a number of cognitive tasks.…”
mentioning
confidence: 98%